Rural Electrification, the Credibility Revolution, and the Limits of Evidence-Based Policy - Jörg Ankel-Peters; Christoph M. Schmidt (Institute for Replication (I4R), 2024)
The so-called credibility revolution dominates empirical economics, with its promise of causal identification to improve scientific knowledge and ultimately policy. By examining the case of rural electrification in the Global South, this opinion paper exposes the limits of this evidencebased policy paradigm. The electrification literature boasts many studies using the credibility revolution toolkit, but at the same time several systematic reviews demonstrate that the evidence is divided between very positive and muted effects. This bifurcation presents a challenge to the science-policy interface, where policymakers, lacking the resources to sift through the evidence, may be drawn to the results that serve their (agency's) interests. The interpretation is furthermore complicated by unresolved methodological debates circling around external validity as well as selective reporting and publication decisions. These features, we argue, are not particular to the electrification literature but inherent to the credibility revolution toolkit.
Keywords: O13; D78; 330; Energy access; evidence-based decision-making; systematic reviews; meta-science